Citation Analysis of Business Research: An International Journal in the Field of Business - Fatima, Nishat (DESIDOC Journal of Library & Information Technology, 2017)
The present study is citation analysis of Business Research. It covers 18 issues of 9 volumes of Business Research published bi-annually during the period 2008-2016. The analysis covers the study of citation pattern and chronological growth citations. It also covers authorship pattern of the articles and various information sources of cited material. On the basis of citation analysis, a rank list of journals is prepared and core journals in the field of Business research are identified. Similarly, core areas of research are identified. The study reveals that researchers have cited journals (77.33%) more than books, editorial works and all other sources of information. Growth in collaborative trend of writing papers is also noticed as citations contributed by two authors is (37.67%) and single authors is (33.42%) followed by three authors (21.59%). Half-life of journal’s citations is found to be fourteen years. Bradford’s law doesn’t found fit in the study. Academy of Management Journal (157 citations), Strategic Management Journal (141 citations) and The Journal of Finance (136 citations) are the most cited journals. Supply chain management and advertising are the two main areas of research among researchers.